IMPLEMENTASI FUNGSIONALISME STRUKTURAL TALCOTT PARSONS DALAM UPAYA MELESTARIKAN TRADISI ISLAM MELAYU NGANGGUNG DULANG DI BANGKA BELITUNG - Aprilia, Sindi; Juniarti, Umi (JURNAL DIALOKA: Jurnal Ilmiah Mahasiswa Dakwah dan Komunikasi Islam, 2022)
Nganggung culture or was called Sepintu Sedulang is an activity that carried the dulang of food to the mosque or musholla in Bangka Belitung. Culture is not passed on through genetics, but through leasrning.The article was designed to learn the role of each element of society structurally in trying to preserve the traditions of accountability. The theory used in this writing is the theory of a structural functionality with a Talcott Parsons figure with an AGIL scheme it offers. The result is in structural functionality, traditions held in place five elements, purpose, means, requirements, norms and efforts. The five elements are a combination of both external factors and the subjective process of tradition subject. In the AGIL scheme it consists of four subsystems, that is adaptation, goals, unity, and maintenance of patterns. The scheme is then implemented to elements of society, where achieving the purpose of preserving culture requires a concerted effort to build multiculticultural awareness in individuals. Thus, the enduring traditions of ingratitude can still be maintained and maintained.